Allometric relationships, functional differentiations, and scaling of growth rates across 151 tree species in China. Issue 5 (16th May 2021) - Zhao, Meifang; Tian, Shihong; Zhu, Yu; Li, Zhiqiang; Zeng, Suping; Liu, Shuguang
Abstract: Chinese trees adapted to wet, warm, highly heterogeneous, and dynamic light environments might be expected to systematically differ from other non‐Chinese trees based on stem allometry and life em allo. However, our understanding of the extent to which how differentiation in forest architecture and species size influences tree allometry relates to fundamental physiological and ecological trade‐offs, climate, forest structure, and function is limited. We quantified height–diameter allometries and growth increments of 13, 594 individuals of 151 tree species across China. Although trees grew statistically indistinguishably from the theoretically predicted exponent, the height–diameter allometries for trees in China deviated from tree patterns in other continental forests worldwide. Chinese trees showed substantially lower heights at a given diameter for larger trees and asymptotic heights (33.05 m), with values were 5.5% to 43.3% lower than those estimated for continental rain forest trees in South America, Australia, Southeast Asia, and Africa. In total, 149 of 151 species showed significant nonlinearity of height–diameter allometry with asymptotic heights ranging from 6.33 to 50.54 m; additionally, half (74/149 species) fell in the range of 20–33.5 m, averaging 21.98 ± 8.70 m (SE) for canopy trees. In subsets of canopy trees sampled from larger‐statured species and deciduous trees, the approximated maximum heights were 14–42% larger than those of smaller‐statured and evergreens and those in other wet and warmer regions found worldwide. These results suggest flexible phenotypic responses of height–diameter allometries to heterogeneous light conditions along understory‐canopy gradients. Average growth rates, varying from 0.02 to 0.78 cm/yr (mean of 0.25 cm/yr), were positively related to the asymptotic height, diameter at inflection, and allometric intercept but negatively correlated with the shape of the asymptotic curve and allometric slope. Species with asymptotic heights above 30 m or inflection sizes larger than 20 cm clearly depicted higher growth rates than smaller ones.